Integrating STEAM Principles in E-Book Design for Game Development Learning: A Systematic Literature Review - Vienda Miccela Seldry; Wisnu Djatmiko; C Rudy Prihantoro (PT. Anagata Sembagi Education, 2025)
The integration of Science, Technology, Engineering, Arts, and Mathematics (STEAM) principles into digital learning resources has gained increasing attention in secondary education, particularly in game development learning at Phase F (Grade XI). This study aims to systematically review the literature on the design and pedagogical implementation of STEAM-based e-books for game development education. A systematic literature review was conducted by analysing peer-reviewed journal articles indexed in major academic databases, including Scopus, Web of Science, ERIC, and Google Scholar, published between 2015 and 2024. The selected studies were screened using predefined inclusion and exclusion criteria and analysed through qualitative thematic synthesis. The findings indicate that STEAM-based e-books commonly integrate interdisciplinary problem-solving tasks, interactive multimedia elements, and project-oriented learning activities that support conceptual understanding and the development of creative skills in game design. Reported learning outcomes include improved student engagement, enhanced computational and design thinking skills, and increased collaboration and creativity. However, the review also reveals gaps in empirical validation, long-term learning impact, and alignment with secondary-level curriculum standards. This study contributes to the pedagogical discourse by synthesising current evidence on STEAM-oriented e-book design. It offers recommendations for educators, instructional designers, and future research in digital game development learning.